Impact evaluation of the Alliance for a Caries-Free Future. Demonstrative territory, communa 20 of Cali - García-Zapata, Lina María; Bergonzoli, Gustavo (Revista Facultad de Odontología Universidad de Antioquia, 2022)
Introduction: in 2010, the first chapter of the Alliance for a Caries-Free Future was established in Colombia with a group of leaders in dentistry interested in generating contextualized intervention strategies that would allow integrating the elements of the Health System to guarantee dental caries-free communities with actions aimed at the early childhood population. The objective was to evaluate the impact of the Alianza project on children under 5 years of age who intervened in Comuna 20 of Cali during the period 2011 to 2018. Methods: based on the RE-AIM framework coverage, effectiveness, adoption, implementation, maintenance and access, were identified to know the impact of keeping children free from cavitation cavities. Results: 89% of the population under 5 years of age has benefited from educational actions and the application of fluoride varnish, increasing the caries-free population from 34 to 57%, the project has been maintained thanks to the teaching-service agreement and the intersectoral workspaces. 54% of the children visited at home have had access to individual care services by a dentist, only 30% of the initial protocol was maintained under the Family Health strategy. Conclusions: the project has allowed the articulation of actions, resources, and wills for the development of inter-institutional actions in favor of oral health of the early childhood population, in the time evaluated, a significant advance is evidenced in the individual and population indicators with the active and permanent participation of Cali institutions in this alliance. <br style="font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-align: -webkit-auto; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px;" />